2020
DOI: 10.3390/cancers12103001
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Instability in Circulating Tumor Cells

Abstract: Circulating tumor cells (CTCs) can promote distant metastases and can be obtained through minimally invasive liquid biopsy for clinical assessment in cancer patients. Having both genomic heterogeneity and instability as common features, the genetic characterization of CTCs can serve as a powerful tool for a better understanding of the molecular changes occurring at tumor initiation and during tumor progression/metastasis. In this review, we will highlight recent advances in the detection and quantification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 151 publications
(261 reference statements)
0
7
0
Order By: Relevance
“…However, our data showed that sSMC cells have higher instability and a different cell cycle dynamic compared with normal cells. We also showed that these cells exhibit telomeric instability, which enables development of tumors and progression of tumor cells to adapt selectively to different environmental pressures resulting in intratumoral cell heterogeneity ( 9 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, our data showed that sSMC cells have higher instability and a different cell cycle dynamic compared with normal cells. We also showed that these cells exhibit telomeric instability, which enables development of tumors and progression of tumor cells to adapt selectively to different environmental pressures resulting in intratumoral cell heterogeneity ( 9 ).…”
Section: Discussionmentioning
confidence: 96%
“…At a cellular level, genomic imbalances such as aneuploidy and microsatellite instability (MSI), and changes in chromosome structure (duplication, deletion, and translocation) are markers of genomic or chromosomal instability (CIN) ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specific telomere profiles are associated with disease stability vs. progression [ 18 , 21 , 22 , 23 , 24 , 25 ]. Critically short telomeres, telomere dysfunction, and fusions have all been correlated with disease progression [ 18 , 25 , 27 , 28 , 29 ]. Therefore, telomere profiling may represent both a clinically useful prognostic tool and a potential guide for therapeutic intervention [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, including increased glucose uptake, angiogenesis, an altered tumor microenvironment (TME) and a cell's ability to avoid immune surveillance via masking of checkpoint inhibitors such as PD-L1, may allow invasion of these genetically and phenotypically abnormal cells into the blood stream where they present as circulating tumor or CTCs. One of the hallmarks of CTCs is genetic heterogeneity and genomic or chromosomal instability (CIN) [33]. CIN includes microsatellite instability (MSI), chromosome structural variations such as deletions, duplications and translocations, as well as chromosome number.…”
Section: Pathogenesis Of Ctcsmentioning
confidence: 99%
“…Aneuploidy, due to errors in chromosomal segregation, is a consequence of CIN and is implicated in tumorigenesis as evidenced by the increased rate of malignancies found in patients with global or mosaic aneuploidies. The knowledge that aneuploidy is a sine qua non or essential element of a malignant cell forms the basis of certain LB tests that rely on the demonstration of aneuploidy to detect CTCs or CACs (cytogenetically abnormal cells [24,25,33,34]. Genetic mutations arising in CTCs can be characterized by polymerase chain reaction (PCR) or next generation sequencing (NGS) on a single cell basis as well as by fluorescencein-situ-hybridization (FISH) and immunohistochemistry.…”
Section: Pathogenesis Of Ctcsmentioning
confidence: 99%